Implementation of Total Quality Management (TQM) in Improving Product Quality in Manufacturing Companies - Afryilia, Mauldya (Maroon Journal De Management, 2025)
This study examines the implementation of Good Governance principles in the regional budget management of Bali Province, focusing on transparency, accountability, and public participation. By analyzing the effectiveness of these governance reforms, the study reveals significant improvements in the management of public funds, leading to better resource allocation and increased public satisfaction. The research compares the current practices with established frameworks of good governance, showing that the application of these principles in local government operations leads to enhanced fiscal responsibility and public trust. Moreover, the study underscores the importance of participatory budgeting and transparent financial reporting as key mechanisms for fostering accountability. The findings contribute to the broader discourse on governance reforms in regional public administration and offer practical insights for policymakers aiming to strengthen governance in similar contexts.